2022
DOI: 10.1007/s11356-021-18333-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of eco-toxic effects of commonly used water disinfectant on zebrafish (Danio rerio) swimming behaviour and recovery responses: an early-warning biomarker approach

Abstract: Eco-toxicity profiles for commonly used disinfectants were lacking. Available traditional toxicity techniques have some limitations (assessments and ethical issues). Behaviour toxicology is a promising research area towards early warning and non-invasive approaches. We studied the potential eco-toxic effects of sodium hypochlorite (NaOCl) on the swimming behaviour of zebrafish. Zebrafish were exposed to different concentrations (Treatment I, Treatment II, Treatment III, and Treatment IV) of NaOCl for 360 h. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 59 publications
(58 reference statements)
0
12
0
Order By: Relevance
“…The behavioural effects of contaminants to aquatic invertebrates depend on the level or duration of exposure and may include no effect, stimulation, acclimation or adaptation, toxic effect, and sometimes readjustment. 61,62 The changes in behaviour upon contamination may also be influenced by changes in the physical and developmental needs of the organisms, e.g. , need for food, search for protection, or preparation for reproduction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The behavioural effects of contaminants to aquatic invertebrates depend on the level or duration of exposure and may include no effect, stimulation, acclimation or adaptation, toxic effect, and sometimes readjustment. 61,62 The changes in behaviour upon contamination may also be influenced by changes in the physical and developmental needs of the organisms, e.g. , need for food, search for protection, or preparation for reproduction.…”
Section: Resultsmentioning
confidence: 99%
“…The behavioural effects of contaminants to aquatic invertebrates depend on the level or duration of exposure and may include no effect, stimulation, acclimation or adaptation, toxic effect, and sometimes readjustment. 61,62 The changes in behaviour upon contamination may also be influenced by changes in the physical and developmental needs of the organisms, e.g., need for food, search for protection, or preparation for reproduction. 61 While acute exposure to the particles alone temporarily induces stress, [51][52][53][54] it can be speculated that as the organisms become aware of the presence of the particles either through accumulation in their digestive tracts or hindrance to their movements, they may attempt to swim away from the contaminated environment, particularly after prolonged exposure as in the case of the chronic tests, hence leading to Environmental Science: Nano Paper increased heart rate and swimming speed.…”
Section: Toxicity Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zebrafish embryo test Crude oil component [25] Danio rerio long-term exposure Metformin [26] Zebrafish antagonistic test Deltamethrin [27] Adult zebrafish behavioral test Cannabinoids [28] Early life stage zebrafish assay Sediment [29] Acute-Chronic test Lead [30] Early life stage zebrafish assay Sodium Hypochloride [31] Combined toxicity test Agrochemicals [32] Adult zebrafish behavioral test Triclosan [33]…”
Section: Test Type Exposure-pollutant Referencesmentioning
confidence: 99%
“…Another recent study of Won et al [40] found that exposure to disinfectants such as chloroxylenol (PCMX) and benzalkonium chloride changed the activities of antioxidant enzymes such as superoxide dismutase and catalase and increased reactive oxygen species even at low concentrations in a rotifer Brachionus koreanus. Ren et al [41] found ecotoxic effects of sodium hypochlorite (NaOCl) on the swimming strength, avoidance behavior, and other anomalies in zebrafish exposed to NaOCl a common disinfectant.…”
Section: Toxic Effects On Aquatic Ecosystemmentioning
confidence: 99%